THU0606 Cognitive dysfunction in connective tissue diseases. (15th June 2017) - Dima, A; Groseanu, L; Balanescu, A; Predeteanu, D; Opris-Belinski, D; Borangiu, A; Mazilu, D; Bojinca, V; Ionescu, R
Abstract : Background: Several studies documented the presence of cognitive dysfunction in different rheumatologic autoimmune diseases, but the absence of standard criteria of diagnostic and of an index with patients in which this dysfunction occurs, makes the mentioned studies often lead to divergent conclusions. Objectives: To evaluate the impact of four autoimmune diseases:Systemic Lupus Erythematosus (SLE), Rheumatoid Arthritis (RA), Systemic Sclerosis (SSc) and Ankylosing Spondylitis (AS) on patient cognition and to identify potential factors which lead to cognitive dysfunction occurrence in this diseases. Methods: This is a case-control study that included randomly selected patients with SLE, RA, SSc and AS from a University hospital and a matched control group. Data collected included: demographics, patients' education and specific data related to disease (duration, activity scores: DAS284v for RA patients, BASDAI in patients with AS, SLICC/SLEDAI for SLE patients and EUSTAR score/Rodnan score for SSc patients, damage indexes, organ involvement, treatment) and comorbidities. Cognition was assesed using MoCA Test (Montreal Cognitive Assessment The Test). The data were then processed using SPSS 23 version software. Results: The study group included 255 patients: 58 RA patients, 52 SLE, 70 SSc and 25 AS patients and 50 healthy matched controls. In all groups of patients, cognitive dysfunction prevalence was higher than control group (RA-64.98%, SLE -57.69%, SS -44.29%, AS -35.72% vs. 24% in the control group). The differences were statistically significant for the RA group (p=0.00), the SLE group (p=0.001), and the SS group (p=0.001). For the RA group none of the items analyzed (demographics, disease characteristic, patient` education) showed a significant correlation with cognitive dyfunction. The same lack of correlation was also noted in AS and SSc patients. For the SLE group the only variable analyzed with a significant impact statistically was the SLEDAI score over 12 (p=0.002). Also, this study did not find a significant statistically association between the presence of antiphospholipid syndrome. Cognitive dysfunction seems to be more frequent and severe in RA and SLE patients compared to AS patients (p=0.014, respectively p=0.05). Conclusions: The results obtained in this study show that, indeed, cognitive dysfunction is an issue to be watched very carefully in patients with autoimmune diseases. The appearance of cognitive dysfunction has a negative impact on life quality of these patients, the pathophysiological mechanisms that contribute to it's appearance are intricate and difficult to isolate. References: Sabbadini MG, Manfredi AA, Bozzolo E, et al. Central nervous system involvement in systemic lupus erythematosus patients without overt neuropsychiatric manifestations. Lupus 1999; 8: 11–19. L. Groseanu, T. Gudu, R. Ionescu. Significance of cognitive impairment in systemic sclerosis. Ann Rheum Dis2016;75(Suppl2): 526. Appenzeller S, Bertolo MB, Costallat LT. Cognitive impairment in rheumatoid arthritis. Methods Find Exp Clin Pharmacol 2004;26:339–43. Disclosure of Interest: None declared